Epitaxial growth and defect repair of heterostructured CuInSexS2−x/CdSeS/CdS quantum dots. Issue 41 (1st October 2019) - Wang, Chao; Barba, David; Zhao, Haiguang; Tong, Xin; Wang, Zhiming; Rosei, Federico
Abstract : Heterostructured quantum dots (hetero-QDs) have outstanding optical properties and chemical/photostability, which make them promising building blocks for use in various optoelectronic devices. Abstract : Heterostructured quantum dots (hetero-QDs) have outstanding optical properties and chemical/photostability, which make them promising building blocks for use in various optoelectronic devices. Here, CuInSe x S2− x /CdSeS/CdS hetero-QDs were synthesized through a facile two-step method. Their particle size, three-dimensional (3D) shapes and the epitaxial relationship between the CuInSe x S2− x /CdSeS core and CdS shell were investigated by high-resolution transmission electron microscopy (HRTEM). Our investigation proves that the as-synthesized hetero-QDs have a regular tetrahedron 3D shape with four {111} crystal facets. The epitaxial relationship between the CuInSe x S2− x /CdSeS core and CdS shell is determined to be [110]core //[110]shell, {112}core //{111}shell . In situ HRTEM observations show that the screw dislocation inside the hetero-QDs can be efficiently repaired using e-beam irradiation. These results may help in designing hetero-QDs with high-quality interfaces and identifying the strategies for synthesizing defect-free hetero-QDs.